Safety and efficacy of intravesical instillation of resiniferatoxin in healthy cats: A preliminary study - Barletta, Michele; Gordon, Julie; Escobar, André; Mitchell, Krista; Trenholme, H. Nicole; Grimes, Janet A.; Jiménez-Andrade, Juan M.; Nahama, Alexis; Cisternas, Alvaro (Frontiers in Veterinary Science, 2023)
Objectives: To evaluate the safety of intravesical application of resiniferatoxin (RTX) in healthy cats and its effects on calcitonin gene-related peptide (CGRP) and substance P (SP) produced by C-fibers. Methods: Seven adult female cats received either 25 mL of saline (control; n = 1,) or intravesical RTX at 5 µg, 25 µg, or 50 µg in 25 mL of saline to a final concentration of 0.2 µg/mL (318 nM), 1 µg/mL (1,591 nM), and 2 µg/mL (3,181 nM) (n = 2 per group). The treatment was instilled into the urinary bladder for 20 minutes. Plasma concentrations of RTX were measured at 0, 0.5, 1, and 4 hours. Physical exam, complete blood count, and serum biochemical analysis were performed on day 0, 7, and 14. After 14 days, the sacral dorsal root ganglia (DRG) and the urinary bladder were harvested for histological and immunofluorescence analysis. Results: Intravesical RTX was well tolerated and plasma concentrations were below the quantifiable limits except for one cat receiving 1 µg/mL. Mild to moderate histopathological changes, including epithelial changes, edema, and blood vessel proliferation, were observed at lower doses (0.2 and 1 µg/mL), and were more severe at the higher dose (2 µg/mL). C-fiber ablation was observed in the urinary bladder tissue at all doses, as shown by an apparent reduction of both CGRP and SP immunoreactive axons. Conclusion: A dose of 25 µg (1 µg/mL) of RTX instilled in the urinary bladder of healthy cats appeared to decrease the density of SP and CGRP nerve axons innervating bladder and induced moderate changes in the bladder tissue.